The Key Directions of Improvement of the Status of the Socio-Ecological Sphere of Corporate Social Responsibility of Coal Mining Enterprises in the State-Owned Sector - Kramchaninova Maiia D.; Gorlova Nataliia M.; Romanova-Malynovska Nataliia Yu. (Bìznes Inform, 2018)
The article is aimed at defining the relationships between the State, society and enterprises of coal industry and researching the perspective directions of improvement of the status of the socio-ecological sphere of corporate social responsibility of the State-owned coal mining enterprises as the most significant in terms of fulfilling their obligations to the State and society. It is identified that coal mining enterprises are generally socially responsible towards the community in which they operate, in view of ensuring the efficiency, employment, and compliance with the law. In the operation, the coal mining enterprises need to define and consider the economic, social, ecological aspects together with interests of their activities. On results of the research, the authors propose the ecological-economic activities as to modernization of coal mining enterprises of the State-owned sector in terms of implementation of the concept of social responsibility, introduction of which will bring both the purely economic and the socio-economic effect in favor of coal mining enterprises, society and the State.